Clinical and cost-effectiveness of Knee Arthroplasty versus Joint Distraction for Osteoarthritis (KARDS): protocol for a multicentre, phase III, randomised control trial - Deborah D Stocken; Dennis G McGonagle; David Murray; Catherine Reynolds; Catherine Fernandez; David R Ellard; Andrew Metcalfe; Hemant Sharma; Paul Harwood; Hamish Simpson; Hemant Pandit; Susanne Arnold; et al. (BMJ Open)
Introduction Knee replacement (KR) is a clinically proven procedure typically offered to patients with severe knee osteoarthritis (OA) to relieve pain and improve quality of life. However, artificial joints fail over time, requiring revision associated with higher mortality and inferior outcomes. With more young people presenting with knee OA and increasing life expectancy, there is an unmet need to postpone time to first KR. Knee joint distraction (KJD), the practice of using external fixators to open up knee joint space, is proposed as potentially effective to preserve the joint following initial studies in the Netherlands, however, has not been researched within an NHS setting. The KARDS trial will investigate whether KJD is non-inferior to KR in terms of patient-reported postoperative pain 12 months post-surgery.Methods and analysis KARDS is a phase III, multicentre, pragmatic, open-label, individually randomised controlled non-inferiority trial comparing KJD with KR in patients with severe knee OA, employing a hybrid-expertise design, with internal pilot phase and process evaluation. 344 participants will be randomised (1:1) to KJD or KR. The primary outcome measure is the Knee Injury and Osteoarthritis Outcomes Score (KOOS) pain domain score at 12 months post-operation. Secondary outcome measures include patient-reported overall KOOS, Pain Visual Analogue Scale and Oxford Knee Scores, knee function assessments, joint space width, complications and further interventions over 24 months post-operation. Per patient cost difference between KR and KJD and cost per quality-adjusted life year (QALY) gained over 24 months will be estimated within trial, and incremental cost per QALY gained over 20 years by KJD relative to KR predicted using decision analytic modelling.Ethics and dissemination Ethics approval was obtained from the Research Ethics Committee (REC) and Health Research Authority (HRA). Trial results will be disseminated at clinical conferences, through relevant patient groups and published in peer-reviewed journals.Trial registration number ISRCTN14879004; recruitment opened April 2021.